Accountability of independent directors: Evidence from firms subject to securities litigation - Brochet, Francois; Srinivasan, Suraj (Journal of Financial Economics, 2014)
We examine which independent directors are held accountable when investors sue firms for financial and disclosure-related fraud. Investors can name independent directors as defendants in lawsuits, and they can vote against their reelection to express displeasure over the directors’ ineffectiveness at monitoring managers. In a sample of securities class action lawsuits from 1996 to 2010, about 11% of independent directors are named as defendants. The likelihood of being named is greater for audit committee members and directors who sell stock during the class period. Named directors receive more negative recommendations from Institutional Shareholder Services, a proxy advisory firm, and significantly more negative votes from shareholders than directors in a benchmark sample. They are also more likely than other independent directors to leave sued firms. Overall, shareholders use litigation along with director elections and director retention to hold some independent directors more accountable than others when firms experience financial fraud.